Feeling the HEAT: Using Hourly Emergency Activity Tracking to demonstrate a novel method of describing activity and patient flow. (23rd December 2016) - Bein, Kendall J; Berendsen Russell, Saartje; Muscatello, David; Chalkley, Dane; Ivers, Rebecca; Dinh, Michael M
Abstract: Objective: The objective of the present study is to demonstrate a novel method of mapping ED activity to analyse patterns presentations, occupancy and performance trends. Methods: This was a retrospective, descriptive analysis of de‐identified and linked ED presentations across NSW, Australia, over five calendar years, 2010–2014. It was undertaken as part of the Demand for Emergency Services Trend in Years 2010–2014 (DESTINY) study. The DESTINY project analysed 10.8 million presentations during 2010–2014. Hourly Emergency Activity Tracking (HEAT) maps were generated to visually represent and analyse the number of emergency arrivals to ED occupancy and proportion of patients leaving the ED within 4 h per hour of day across consecutive months of the year. Results: HEAT maps provided a means of visually representing ED activity to demonstrate hour‐to‐hour trends in presentations, occupancy and performance between 2010 and 2014. This analysis has shown that the most marked increase in presentations per hour has occurred during the 10.00–14.00 hour period, associated with an improvement in ED performance during the same period. Conclusion: HEAT maps may be used to facilitate further analyses of ED demand, patterns of patient presentations and patient flow and future health system redesign.